The DXO decapping exonuclease is a restriction factor for RNA viruses - Lynch, Erin R., author; Geiss, Brian, advisor; Wilusz, Jeffrey, committee member; Perera, Rushika, committee member; Stasevich, Tim, committee member (Colorado State University. Libraries, 2019)
Cellular RNA exonucleases, such as XRN1 and DXO, aid in the destruction of defective cellular mRNAs and help maintain overall cellular health. The RNA decay system, however, also serves another purpose – degrading viral RNAs. The XRN1 exonuclease is known to be a major antagonist of RNA virus genomes, but the role of other cellular RNA decay enzymes in controlling viral infection is less clear. The cellular 5' decapping exonuclease DXO is able to recognize, de-cap, and degrade RNAs lacking 2'-O-methylation on the first nucleotide after the 5' cap, helping the cell to discriminate self from non-self RNAs. Preliminary data we have developed indicate that flaviviruses and alphaviruses replicate to much higher levels in DXO deficient cells than in cells containing DXO, indicating that DXO may also act as a cellular viral restriction factor. Interestingly, flavivirus genomes contain a 5' cap that is generally 2'-O-methylated at the first base of the transcript, providing a potential mechanism to evade DXO degradation. Overall, our results indicate that the DXO decapping exonuclease helps control the replication of positive strand RNA viruses in cells and represents a new viral restriction factor.
Keywords: antiviral; flavivirus; alphavirus; RNA decay; DXO